PENGARUH WORK FROM HOME, KOMITMEN, DAN MOTIVASI, TERHADAP KINERJA ANGGOTA DPRD KABUPATEN TANAH DATAR MASA PANDEMI COVID-19 - Alfi Rahmi HS; Rizal Rizal; Rizal Fahlevi (IAIN Batusangkar, 2023)
This study aims to find out and analyze the effect of work from home, commitment and motivation to the performance of Tanah Datar Regency DPRD members. The type of research used in this study is research with a quantitative approach, with a research instrument in the form of a questionnaire with 35 respondents of Tanah Datar Regency DPRD members. Sampling technique using total sampling. Data analysis techniques using SPSS version 26, classical assumption test, multiple linear regression test, coefficient of determination and hypothesis test. The results showed that work from home partially had a significant effect on the performance of Tanah Datar Regency DPRD members during the Covid-19 Pandemic period, proven t-test obtained by tcount of 2,953> ttable of 2,039. Commit ment has no partial effect on the performance of Tanah Datar Regency DPRD members during Pandemi Covid-19, proven t-test obtained by tcount of 1,924 < ttable of 2,039. Motivation does not partially affect the performance of Tanah Datar Regency DPRD members during the Covid-19 Pandemi proven t-test obtained by tcount of 0.997 < ttable of 2,039. Furthermore, work from home, commitment and motivation significantly influenced the performance of Tanah Datar Regency DPRD members during Pandemi Covid-19 as evidenced by the F test obtained at Fcount of 20.503 > Ftable of 2.90